ANALISIS MODEL KEPUASAN PENGGUNA JASA TRANSPORTASI KERETA API EKSEKUTIF JURUSAN MALANG JAKARTA - Y. Fitra - Aswara; Fatchur - Rahman; Armanu - Thoyib (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT   All countries have mixed economies, i.e. a combination of a private and public sector. Most of the public services offered to thr public are performed by an agent appointed by the principal (i.e. local or central government). The service offers may or may not be in line with the preferences of the users, i.e. the c1tizents. Public services are offered to the users based on the double principal‑agent relationship, i.e. citizens‑government, and government‑operator. Purposes of this research are to determine the relationships among customer prefrences, customer satisfaction, and customer segments. Research findings indicate that because the low degree of congruence between customer preferences, the public transportation industry offers low utility, i.e. low overall satisfaction score. Heterogeneity in consumer preferences are reflected in different evaluation of service quality areas and drivers of customer satisfaction.   Keywords: Kualitas jasa, Kepuasan konsumen, Industri jasa, jasa Pubik, Transportasi, Perilaku konsumen